NSW education department caught unaware after Microsoft Teams began collecting students’ biometric data - Taylor, Josh (The Guardian, 2025)
Gathering of face and voice data went unnoticed for one month after it was automatically enabled for video conferencing app users in March.
Australia
Keywords: Artificial intelligence (AI); Australia news; Australian education; Child Rights; Computing; Microsoft; Privacy; Technology